Strengthening E-Wallet User Loyalty through Gamification Mechanisms: A Multidimensional Perspective of Perceived Value - Aditya Akbar Riadi; Widowati Widowati; Catur Edi Widodo; Rangga Primadasa (Bright Publisher, 2026)
This study aims to investigate the mechanism of e-wallet user loyalty formation through the integration of gamification elements, specifically by exploring the mediating roles of perceived hedonic and utilitarian values. In an increasingly competitive digital financial landscape, maintaining user retention remains a crucial challenge for service providers. Diverging from prior research that predominantly relies on sufficiency logic, this study adopts a dual-analytic approach by combining Partial Least Squares-Structural Equation Modeling (PLS-SEM) and Necessary Condition Analysis (NCA). This dual-analytic approach provides complementary insights into both the primary drivers and the absolute prerequisites of loyalty in a concise manner. Based on the empirical evaluation using PLS-SEM, the findings reveal that gamification significantly stimulates the enhancement of both users' hedonic and utilitarian values. Furthermore, these two dimensions of perceived value successfully validate their roles as robust mediators in bridging the effect of gamified features toward long-term loyalty commitment. Within this sufficiency equation, hedonic value occupies the position as the predictor with the strongest driving force. However, evaluating the bottleneck matrix through the NCA algorithm uncovers complementary theoretical dynamics. The necessity evaluation postulates that utilitarian value—rather than hedonic value—acts as the highest floor limit and the most fundamental prerequisite. The absence of guaranteed functional benefits and economic advantages will inevitably collapse the entire retention scheme, regardless of how visually attractive or entertaining the gamified features are presented. Comprehensively, the conclusions of this research provide academic and managerial justifications that retention management tactics cannot be executed asymmetrically. To secure user loyalty at the maximum level, e-wallet developers are obliged to orchestrate a balanced ecosystem; the stability of practical utility must be secured as the primary foundation before maximizing investments in visual interactivity and entertainment sensations.